2016
DOI: 10.1136/bjsports-2016-096065
|View full text |Cite
|
Sign up to set email alerts
|

Diastasis recti abdominis during pregnancy and 12 months after childbirth: prevalence, risk factors and report of lumbopelvic pain

Abstract: Background/aimDiastasis recti abdominis (DRA) is defined as a separation of the 2 muscle bellies of rectus abdominis. To date there is scant knowledge on prevalence, risk factors, and consequences of the condition. The present study aimed to investigate the prevalence of DRA during pregnancy and post partum, presence of possible risk factors, and the occurrence of lumbopelvic pain among women with and without DRA.MethodsThis prospective cohort study followed 300 first-time pregnant women from pregnancy till 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
246
2
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(273 citation statements)
references
References 36 publications
(46 reference statements)
7
246
2
18
Order By: Relevance
“…The size of IRD decreased from 64.6 mm (SD 19.00) to 15.3 mm (SD 8.4), similarly the prevalence of DRA decreased from 100% to 39.3%. A higher percentage of DRA occurrence at 6 months postpartum was reported by Sperstad et al [14]. In the group of 300 women it amounted to 45.4 %, and decreased to 32.6% at 12 months postpartum.…”
Section: Diastasis Recti Abdominismentioning
confidence: 56%
See 2 more Smart Citations
“…The size of IRD decreased from 64.6 mm (SD 19.00) to 15.3 mm (SD 8.4), similarly the prevalence of DRA decreased from 100% to 39.3%. A higher percentage of DRA occurrence at 6 months postpartum was reported by Sperstad et al [14]. In the group of 300 women it amounted to 45.4 %, and decreased to 32.6% at 12 months postpartum.…”
Section: Diastasis Recti Abdominismentioning
confidence: 56%
“…Some studies, however, deny these statements. Sperstad et al [14] reported no difference between women with and without DRA in prevalence of low back pain, similarly as Mota et al [13] and Parker et al [21]. In Norwegian study, women with DRA did not have a weaker pelvic floor muscle or more pelvic floor dysfunctions than women without diastasis [22].…”
Section: Diastasis Recti Abdominismentioning
confidence: 79%
See 1 more Smart Citation
“…Sin embargo, lo más frecuente es que la DR se presente en el adulto joven, especialmente en la mujer tras el embarazo 3 . La revisión de la bibliografía publicada no muestra trabajos exclusivos sobre el tratamiento de este problema, excepto publicaciones realizadas en centros de estética que ofrecen tratamientos mediante ejercicios que supuestamente mejoran el defecto, pero sin ningún tipo de evidencia científica.…”
Section: Discussionunclassified
“…A lombalgia no puerpério pode apresentar diversos fatores predisponentes. A diástase dos músculos retos abdominais, desencadeada na gestação, compromete a capacidade da musculatura abdominal de estabilização do tronco, interferindo no alinhamento postural e no equilíbrio da musculatura lombar 7 , bem como nas atividades do cotidiano. Assim como a diástase dos músculos retos abdominais, a incisão cirúrgica da cesárea também contribui para a redução da ação da musculatura abdominal como estabilizadora de tronco, contribuindo para susceptibilidade à lombalgia.…”
Section: Tabelaunclassified